Analisis Kecemasan Mahasiswa Pendidikan Bahasa Arab dalam Ujian Akhir Semester Mata Kuliah Qiroatul Kutub - Choirunnisa Marwa Nurul Amin; Musnia Musnia; Uzmatu Ruqoyah; Indah Permatasari; Wahyu Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the level of anxiety of Arabic Language Education students towards the Final Semester Exam of Qiraatul Kutub course. The method used in this study was a questionnaire survey distributed to Arabic Language Education students at one of the universities. The data obtained were analyzed descriptively to identify factors that influence anxiety levels, as well as their impact on students' academic achievement. The results showed that most students experienced moderate levels of anxiety, with the main causative factors being academic pressure, lack of preparation, and environmental expectations. These findings are expected to enable lecturers to design more effective support programs to help students overcome academic anxiety, so that they can improve their academic achievement during exams in the Qiraatul Kutub course. The method used in this study was a quantitative survey by distributing questionnaires to 10 Arabic Language Education students at UIN SMH Banten. The questionnaire included 10 items that measured anxiety levels based on a Likert scale of 1 to 4. The results of the analysis showed that 65% of respondents felt high levels of anxiety, 25% had moderate levels of anxiety, and 10% had low levels of anxiety. Factors contributing to anxiety include lack of preparation (70%), pressure from expectations from parents and teachers (60%), and lack of social support (55%). In addition, 80% of students with high levels of anxiety admitted to having difficulty managing their study time, and 75% of them felt doubtful about their own abilities. academic.